Energy Efficiency Dynamics and Climate Policy - Gregory Casey; Yang Gao (CESifo GmbH, 2024)
We study the effectiveness of climate change mitigation policies in reducing carbon emissions, focusing on the channel of economy-wide energy efficiency. Using U.S. data, we estimate impulse response functions (IRFs) that characterize how energy efficiency responds to energy price shocks. Standard climate-economy models cannot replicate the slow transition dynamics observed in the data. We build a tractable model that nests the existing literature and can closely replicate the empirical IRFs. The slow dynamics in our model imply that carbon taxes reduce cumulative emissions less than predicted by standard models and that clean energy subsidies reduce cumulative emissions more than predicted by standard models.
Keywords: E24; O33; O44; 330; climate change; climate policy; energy efficiency